2018
DOI: 10.1002/ppul.23933
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of lung function in extremely prematurely born children

Abstract: These results demonstrate in those born extremely prematurely there is tracking of airway function during childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
3
10
0
1
Order By: Relevance
“…This diversity arises from the complex interaction of structures damaged by oxygen and mechanical ventilation injury in the premature lung and a developmental healing process . However, the main pulmonary features of BPD might be an obstructive lung pattern, as shown in other studies . Since the severity of BPD could be largely related to the degree of airway obstruction, t PEF / t E was found to be a useful airflow limitation marker to assess the severity of the decrease in pulmonary function in BPD, as shown in our study.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This diversity arises from the complex interaction of structures damaged by oxygen and mechanical ventilation injury in the premature lung and a developmental healing process . However, the main pulmonary features of BPD might be an obstructive lung pattern, as shown in other studies . Since the severity of BPD could be largely related to the degree of airway obstruction, t PEF / t E was found to be a useful airflow limitation marker to assess the severity of the decrease in pulmonary function in BPD, as shown in our study.…”
Section: Discussionsupporting
confidence: 79%
“…1 However, the main pulmonary features of BPD might be an obstructive lung pattern, as shown in other studies. [30][31][32][33][34] Since the severity of BPD could be largely related to the degree of airway obstruction, t PEF /t E was found to be a useful airflow limitation marker to assess the severity of the decrease in pulmonary function in BPD, as shown in our study.…”
Section: Discussionsupporting
confidence: 64%
“…As expected, the severity of BPD correlated with the severity of impairment. Lo and colleagues reported parallel decrements of FRC in survivors of preterm birth at 26 weeks that were measured by plethysmography and He‐dilution at age 1 year and age 11‐14 years . The superimposition of rapid weight gain may also contribute in this setting.…”
Section: Demographics and Neonatal Lung Diseasementioning
confidence: 97%
“…Lo and colleagues reported parallel decrements of FRC in survivors of preterm birth at 26 weeks that were measured by plethysmography and Hedilution at age 1 year and age 11-14 years. 21 The superimposition of rapid weight gain may also contribute in this setting. Lowe and colleagues correlated high rates of fetal and infant growth among the prematurely born with postnatally reported wheezing.…”
Section: Demographics and Neonatal Lung Diseasementioning
confidence: 99%
“…Low VmaxFRC was associated with diminished airflow measurements from 6 to 24 years, indicating that low lung function at birth tracks into adulthood. Lo et al measured airway resistance (R aw) and FRC by both body plethysmography (FRC pleth ) and helium gas dilution (FRC He ) in 35 subjects born prematurely with a mean GA of 26 weeks. They found that FRC He :FRC pleth decreased about 0.54% per year and that R aw at 1 year corrected correlated with the results at follow‐up of R aw , FEV1, and FEF 75 .…”
Section: Introductionmentioning
confidence: 99%